Growth mindset and well-being in social interactions: countering individual loneliness - Wang, Chao; Li, Shanshan; Wang, Yilin; Li, Mengxia; Tao, Weidong (Frontiers in Public Health, 2024)
Introduction Loneliness is a prevalent negative emotion experienced by college students. This study explores the relationship between a growth mindset and loneliness among college students. Methods A total of 560 college students completed the Growth Mindset Scale (GMS), UCLA Loneliness Scale (UCLA), Interpersonal Relationships Assessment Scale (IRS), and two measures assessing distinct facets of well-being the Satisfaction with Life Scale (SWLS) and the revised Positive Affect and Negative Affect Scale (PANAS). Results and discussion The results found a significant negative correlation between a growth mindset and loneliness. A growth mindset negatively predicted loneliness through the chain-mediated effects of interpersonal distress and well-being. These findings underscore the important role of a growth mindset in influencing loneliness, providing teachers and practitioners a new perspective to understand and intervene college students’ psychological challenges.